2017
DOI: 10.3390/foods6120104
|View full text |Cite
|
Sign up to set email alerts
|

Consumers in a Sustainable Food Supply Chain (COSUS): Understanding Consumer Behavior to Encourage Food Waste Reduction

Abstract: Consumers are directly and indirectly responsible for a significant fraction of food waste which, for a large part, could be avoided if they were willing to accept food that is suboptimal, i.e., food that deviates in sensory characteristics (odd shape, discoloration), or that has a best-before date which is approaching or has passed, but that is still perfectly fine to eat. The choice to accept or discard suboptimal food is taken either before or after purchase (hence, in the retail store or in the household).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 51 publications
2
49
0
Order By: Relevance
“…Interestingly, 64% of consumers in the EU misinterpret the meaning of the best before date [41]. While consumers often confuse best before and use by dates, they state that they need more information about the shelf life of food once a package has been opened [42].…”
Section: Causes Of Food Losses and Food Waste Related To Packagingmentioning
confidence: 99%
“…Interestingly, 64% of consumers in the EU misinterpret the meaning of the best before date [41]. While consumers often confuse best before and use by dates, they state that they need more information about the shelf life of food once a package has been opened [42].…”
Section: Causes Of Food Losses and Food Waste Related To Packagingmentioning
confidence: 99%
“…It has been found that 15% of all fresh and consumer-friendly food is discarded before it becomes available for sale in supermarkets/stores [5], and producers of fruits and vegetables discard up to 30% because of aesthetic imperfections, meaning that a lot of food is wasted before entering the supermarkets [6]. As an example, of the approximately 30,000 tons of apples produced in Sweden, 7-10% is wasted each year; this does not include all the fruit that is wasted in peoples' gardens.…”
mentioning
confidence: 99%
“…Sustainable eating is therefore essential not only in terms of food and nutrient safety [20,21], but also on the social level [22,23]. That is why numerous recommendations and studies advise to policy makers in food security and sustainability regulation to integrate direct, indirect or voluntary tools into the social framework for sustainable food consumption [20,[24][25][26][27][28][29][30].…”
Section: A Few Aspects Of the Sustainability Dimensionmentioning
confidence: 99%
“…People's food habits are typically characterized by health, supply, consumer culture, family habits passed on from the previous generation, society, the environment and policy frameworks [1,4,28]. Consumer choice of food at present can be determined by whether the product is sustainable or organic.…”
Section: A Short Review Of the Cultural Differences In Sustainable Fomentioning
confidence: 99%